2017
DOI: 10.12973/iji.2017.10120a
|View full text |Cite
|
Sign up to set email alerts
|

A Scale for Measuring Teachers’ Mathematics-Related Beliefs: A Validity and Reliability Study

Abstract: The purpose of this study was to develop and validate a scale of teacher beliefs related to mathematics, namely, beliefs about the nature of mathematics, mathematics teaching, and assessment in mathematics learning. A scale development study was used to achieve it. The draft scale consisted of 54 items in which 16 items related to beliefs about the nature of mathematics, 23 items related to beliefs about the teaching of mathematics, and 15 items related to beliefs about assessment in mathematics learning. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
0
13
0
2
Order By: Relevance
“…As can also be seen in Table 4, the convergent validity was assessed by computing AVE scores. AVE should exceed 0.5 under ideal conditions; Chin (1988), Purnomo (2017) and Yin (2018) suggested that an AVE score of 0.36-0.5 is the acceptable threshold/range for convergent validity [70][71][72]. The AVE scores ranged upward from 0.42, as shown in Table 4, meaning that all constructs had convergent validity.…”
Section: Validity and Reliabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…As can also be seen in Table 4, the convergent validity was assessed by computing AVE scores. AVE should exceed 0.5 under ideal conditions; Chin (1988), Purnomo (2017) and Yin (2018) suggested that an AVE score of 0.36-0.5 is the acceptable threshold/range for convergent validity [70][71][72]. The AVE scores ranged upward from 0.42, as shown in Table 4, meaning that all constructs had convergent validity.…”
Section: Validity and Reliabilitymentioning
confidence: 98%
“…As per Table 4, all constructs were reliable, with both the alpha and CR coefficients ranging upward from 0.74. As all were greater than the suggested minimum of 0.70 [70], all were considered reliable. Moreover, three latent variables and ten observed variables were included, and the reliability test was analyzed using SPSS 26.0.…”
Section: Satisfaction Behavioral Intentions and Competitivenessmentioning
confidence: 99%
“…Uji validitas lembar observasi dari dua validator memperoleh hasil persentase sebesar 83,75% sehingga masuk dalam kategori layak. Uji reliabilitas dalam penelitian ini menggunakan rumus Alpha berbantuan SPSS versi 20 diperoleh hasil sebesar 0,894 sehingga 𝑟 -.&$%/ > 0,60 dan dinyatakan reliabel (Purnomo, 2017;Nunnally & Bernstein, 1994;Clark & Watson, 1995).…”
Section: Hasil Dan Pembahasanunclassified
“…Menurut Hasanuddin (2017) menyatakan bahwa matematika dipandang sebagai hasil akal budi manusia, selain itu ia juga dianggap sebagai hasil abstraksi pikiran manusia. Matematika adalah berasal dari dan untuk keperluan sosial, sehingga melekat dengan budaya manusia (Purnomo, 2016(Purnomo, , 2017a(Purnomo, , 2017bPurnomo et al, 2016).…”
Section: Pendahuluanunclassified